Personality Competencies of Counselor School and Their Impact on Students' Personalities - Rismar Julia Utami (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2021)
The existence of Guidance and Counseling Teachers as one of the educators has the task of developing the potential and independence of students. Therefore, the competence of the BK teacher is needed in shaping the student's personality to become a superior person which is applied in the school environment. The purpose of this study was to determine the personality competencies of BK teachers and their impact on students' personalities. This research was conducted at SMP Negeri 1 Kerinci. The population in this study were 399 students, the sampling technique used proportional random sampling with a sample of 120 people. Furthermore, to determine the extent of the teacher's personality competence, a sample of 3 BK teachers was taken. Methods of collecting data using a questionnaire, a questionnaire about the personality competencies of teachers and students. Data analysis used descriptive percentage analysis. Based on data analysis, it was found that the highest aspect of teacher competence is faith and piety to God Almighty, while the highest aspect of student personality is displaying noble character.